The Effect of Internal Control on Fraud Prevention in the Inspectorate Office Sumedang Regency - Arli Cucun; Tita Kartika; Lilis Kartika (LPPM Universitas Sebelas April, 2020)
The core problem of this research is that the performance of the inspectorate is not optimal in preventing vulnerability. The purpose of this research is to determine the internal control, prevention and internal control that affect prevention at the Sumedang Regency Inspectorate Office. This study uses a descriptive research method approach with quantitative analysis techniques, conducted through a survey method. Data collection techniques were analyzed by means of observation and questionnaires. The research data uses simple regression analysis, correlation test, coefficient of determination and hypothesis testing. The results showed that internal control of 4,637 was very good with an average of 85.87%, vibration prevention was 3.998 good with control of 83.29% and internal control control with control was 0.777 (strong relationship), and the magnitude of the influence of internal control to vulnerability at the Inspectorate Office of Sumedang Regency by 60.4% (strong) and there are still 39.7% of other factors. The results of the calculation of the hypothesis, it turns out that tcount (9.40) > ttable (1.67155), that there is a positive influence between internal control on fraud prevention at the Sumedang Regency Inspectorate Office and can be accepted. The Sumedang Regency Inspectorate Office in order to maintain external pressure by investors can affect the performance of the Sumedang Regency Inspectorate Internal Control and improve in terms of competitive operating conditions